GENOME-WIDE IDENTIFICATION OF TOMATO MICRO-RNAs TARGETING TOMATO LEAF MOLD PATHOGEN - Aydin ATAKAN (Journal of Animal and Plant Sciences, 2025)
Tomato (Solanum lycopersicum L.) belongs to the Solanaceae family and is the second most cultivated and consumed vegetable crop after potato, in the world. Tomatoes, exposed to many pathogens throughout their life cycles, are a model plant for investigating stress responses. Tomato leaf mold disease (TLMD), caused by Cladosporium fulvum, is one of the most harmful foliar diseases of tomato, causing important yield losses. The avirulence genes (Avr) of C. fulvum encode the effector proteins responsible for the pathogenic characteristics of this fungus. Therefore, RNA interference (RNAi) mechanisms can potentially silence these genes. This study aimed to analyze mature sly-miRNAs encoded in the tomato genome with the potential for targeting TLMD Avr genes, using four target prediction algorithms. The objective is to implement in silico predicted miRNAs to induce RNAi-mediated defense responses. Previously identified 147 mature tomato miRNAs were acquired from the primary miRNA repository miRBase and evaluated in terms of hybridization with TLMD Avr gene sequences. The present study aims to analyze tomato miRNAs with predicted potential to target TLMD avirulence genes, based on their hybridization energies and structural properties. Among the 147 tomato miRNAs investigated, four computational algorithms—RNAhybrid, psRNATarget, TapirHybrid, and miRanda—predicted that 29, 17, 30 and 11 tomato miRNAs potentially target Avr genes, respectively. 17 sly-miRNAs were identified to target TLMD sequences using at least two algorithmic tools. Moreover, three algorithmic tools identified only two miRNAs, sly-miR390b-5p and sly-miR319c-5p, as the most effective consensus miRNAs targeting the TLMD sequences. The availability of in silico validated tomato genome-encoded sly-miRNAs with predicted potential to target TLMD in infected tomato plants represents the first step toward developing TLMD-resistant tomato plants. These findings provide important insights into RNAi-mediated silencing of TLMD.
Keywords: Tomato; Cladosporium fulvum; computational algorithms; miRNA; avirulence gene; RNAi